2022
DOI: 10.1177/15593258221128743
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of MgO and MnO Nanoparticles Within the Context of Thyroid Profile and Pancreatic Histology in a Diabetic Rat Model

Abstract: Magnesium oxide (MgO) and manganese oxide (MnO) have been reported to be effective against Diabetes Mellitus (DM). However, their nanoparticulate form has not been evaluated for antidiabetic effect. MgO and MnO nanoparticles (15–35 nm) were synthesized and subsequently characterized by ultraviolet-visible spectroscopy (UV-VIS), zeta sizer, and scanning electron microscopy. 6–7 weeks old rats weighing 200–220 mg were divided into 07 equal groups (n = 8), namely, negative control (NC), positive control (PC), sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Yeğin and Mert (2013) confirmed mice as diabetic if their blood glucose level was above 210 mg/dL (24), Demir and Yılmaz (2013) accepted mice as diabetic if blood glucose level was between 140-200 mg/dL (25), and Kanitkar and Bhonde (2004) verified mice as diabetic if it was 200 mg/dL. In our study, mice with ≥ 200 mg/dL fasting blood glucose level established as diabetic (19).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Yeğin and Mert (2013) confirmed mice as diabetic if their blood glucose level was above 210 mg/dL (24), Demir and Yılmaz (2013) accepted mice as diabetic if blood glucose level was between 140-200 mg/dL (25), and Kanitkar and Bhonde (2004) verified mice as diabetic if it was 200 mg/dL. In our study, mice with ≥ 200 mg/dL fasting blood glucose level established as diabetic (19).…”
Section: Discussionsupporting
confidence: 56%
“…Animals in the diabetic group were fasted for 12-hour to determine 72 hours later blood glucose level. It was considered as diabetic if blood glucose level equal or above 200 mg/dL (19). On the 30 th day of the study, before the tissues were collected, the animals were again fasted for 12 hours and their blood glucose level were measured for the last time.…”
Section: Determination Of Blood Glucose Levelmentioning
confidence: 99%
“…Previous literature studies have reported that the MgONPs with a particle radius of ∼75 nm have a UV−vis absorption peak at 257 nm and those with a radius of 25−35 nm exhibit a peak at 295 nm, which were much distant from the 163 nm peak observed in bulk MgO. 33,63 The MgONPs utilized in this work was ∼50 nm, and thus its UV−vis absorption peak could fall between 257 and 295 nm. This was much lower than the wavelength of 400−500 nm emitted by the light curing unit.…”
Section: Physicochemical Propertiesmentioning
confidence: 76%
“…Studies have suggested that P. gingivalis can contribute to the development of insulin resistance, one proposed mechanism for this effect is through lipotoxicity. Insulin resistance (IR) is associated with lipotoxicity, and chronic inflammation may be a common denominator ( Watanabe et al., 2011 ; Fleetwood et al., 2017 ; Ni et al., 2018 ; Pirih et al., 2021 ; Shaukat et al., 2022 ; Thouvenot et al., 2022 ; Yoshimoto et al., 2022 ). In mice, oral administration of P. gingivalis leads to systemic inflammation, increased adiposity and insulin resistance ( Artese et al., 2015 ; Le Sage et al., 2017 ).…”
Section: Pathogenesis Of Insulin Resistance Caused By P Gin...mentioning
confidence: 99%